Memorandum of Understanding between the Center for Urban Health Equity, James P. Grant School of Public Health and Urban Partnerships for Poverty Reduction (2011) - Center for Urban Health Equity, JPGSPH; Urban Parterships for Poverty Reduction,UPPR (Center for Urban Health Equity and Urban Partnerships for Poverty Reduction, 2013)
Memorandum of Understanding between the Urban Partnerships for Poverty Reduction Program, Having its office at RDEC-LGED Building Level-8, Agargaon, Dhaka 1207, hereinafter referred to as "UPPR". and Center for Urban Health Equity, James Grant School of Public Health, having its office at BRAC University, 66, Mohakhali, Dhaka-1212, Bangladesh.